2013
DOI: 10.3109/09540261.2013.849663
|View full text |Cite
|
Sign up to set email alerts
|

The Cache County Study on Memory in Aging: Factors affecting risk of Alzheimer's disease and its progression after onset

Abstract: The Cache County Study on Memory in Aging is a longitudinal, population-based study of Alzheimer's disease (AD) and other dementias. Initiated in 1995 and extending to 2013, the study has followed over 5,000 elderly residents of Cache County, Utah (USA) for over twelve years. Achieving a 90% participation rate at enrollment, and spawning two ancillary projects, the study has contributed to the literature on genetic, psychosocial and environmental risk factors for AD, late life cognitive decline, and the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 146 publications
(156 reference statements)
0
53
0
2
Order By: Relevance
“…By assimilating information from user inputs and context-aware sensors, the app adapts reminder delivery to improve integration with the user’s lifestyle over time. TAUT is currently is being tested in an elderly, cognitively impaired population,16 following a pilot in healthy younger adults where 73% of reminders were acknowledged within 12.38 seconds 15…”
Section: Presentationmentioning
confidence: 99%
“…By assimilating information from user inputs and context-aware sensors, the app adapts reminder delivery to improve integration with the user’s lifestyle over time. TAUT is currently is being tested in an elderly, cognitively impaired population,16 following a pilot in healthy younger adults where 73% of reminders were acknowledged within 12.38 seconds 15…”
Section: Presentationmentioning
confidence: 99%
“…Developmental psychologists emphasize that social connections are essential to human development (22,23), and social epidemiologists have clearly established that social ties are fundamental to human health (24,25). A substantial literature on bereavement shows that the death of even one family member (whether spouse, child, parent, or sibling) undermines physical health and increases mortality risk (4,26,27). Notably, not all losses have the same effects.…”
mentioning
confidence: 99%
“…Cognitive scores were higher, both at baseline and subsequently, for those consuming ready-to-eat (RTE) cereals more frequently than weekly but less frequently than daily. Daily and nonconsumers of RTE cereals had lower scores (78). In the Women's Health Study, higher whole grain intake (2.2 servings/day) was associated with higher average cognition scores compared with women whose daily intake of whole grains was lower (0.8 servings/day) (79).…”
Section: Breads and Cerealsmentioning
confidence: 88%
“…The study showed that consumption of excess amounts of grain and white bread products and inadequate amounts of dietary fiber were problematic, underscoring the need for dietary balance (75). The benefits of dietary balance were also demonstrated in a study of 4,000 elderly adults in the 12 year Cache County (Utah) Study on Memory Health and Aging (78). Cognitive scores were higher, both at baseline and subsequently, for those consuming ready-to-eat (RTE) cereals more frequently than weekly but less frequently than daily.…”
Section: Breads and Cerealsmentioning
confidence: 95%